“È così che finisce il mondo, non già in un frastuono, ma in un lungo piagnisteo”. Catastrofe e distopia nella nuova serialità narrativa e nell'immaginario videomusicale - Alessandro Alfieri (Philosophy Kitchen, 2019)
The storytelling of the end of the world has always represented in the cultural horizon an essential speculative principle, because the fear for the catastrophe is one of the most effective principles to mark the collective imaginary; in the last years, the perverse attraction for global destruction has been re-launched by popular culture. This essay examines how, in the age of international terrorism, natural cataclysms and economic crisis, several series (The Handmaid’s Tale, Mr. Robot, The Walking Dead) and videos (The Suburbs – Arcade Fire, Incantevole – Subsonica, Waiting for a Sign – Scratch Massive ft. Koudlam), tell us about the collapse of the liberal-democratic system without a positive alternative, where dystopia takes on a metaphorical meaning.